p16Ink4a Prevents the Activation of Aged Quiescent Dentate Gyrus Stem Cells by Physical Exercise - Micheli, Laura; D’Andrea, Giorgio; Ceccarelli, Manuela; Ferri, Alessandra; Scardigli, Raffaella; Tirone, Felice (Frontiers in Cellular Neuroscience, 2019)
In the neurogenic niches – the dentate gyrus of the hippocampus and the subventricular zone (SVZ) adjacent to lateral ventricles – stem cells continue to divide during adulthood, generating progenitor cells and new neurons, and to self-renew, thus maintaining the stem cell pool. During aging the numbers of stem/progenitor cells in the neurogenic niches are reduced. The preservation of the neurogenic pool is committed to a number of antiproliferative genes, with the role of maintaining the quiescence of neural cells. The cyclin-dependent kinase inhibitor p16Ink4a, whose expression increases with age, controls the expansion of SVZ aging stem cells, since in mice its deficiency prevents the decline of neurogenesis in SVZ. No change of neurogenesis is however observed in the p16Ink4a-null dentate gyrus. Here we hypothesized that p16Ink4a plays a role as a regulator of the self-renewal of the stem cell pool also in the dentate gyrus, and to test this possibility we stimulated the dentate gyrus neural cells of p16Ink4a-null aging mice with physical exercise, a powerful neurogenic activator. We observed that running highly induced the generation of new stem cells in the p16Ink4a-null dentate gyrus, forcing them to exit from quiescence. Stem cells, notably, are not induced to proliferate by running in wild-type mice. Moreover, p16Ink4a-null progenitor cells were increased by running significantly above the number observed in wild-type mice. The new stem and progenitor cells generated new neurons, and continued to actively proliferate in p16Ink4a-null mice longer than in the wild-type after cessation of exercise. Thus, p16Ink4a prevents aging dentate gyrus stem cells from being activated by exercise. Therefore, p16Ink4a may play a role in the maintenance of dentate gyrus stem cells after stimulus, by keeping a reserve of their self-renewal capacity during aging.